Application of Round Robin in Scheduling in Web-Based Wedding Organizers - Effendy, Calvin; Gusrianty, Gusrianty (Journal of Applied Business and Technology, 2024)
Wedding are cherished moments in the lives of couples. However, the complexity of wedding planning often poses challenges in arranging event schedules. To address this issue, this study aims to implement the Round Robin method for scheduling in a web-based Wedding Organizer. The Round Robin method is a scheduling algorithm that evenly allocates time for various necessary activities. In the context of a web-based Wedding Organizer, its implementation can optimize wedding activity scheduling by considering available time slots and avoiding scheduling conflicts among vendors. This research involves the development of a web-based application that employs the Round Robin method to organize the schedules of various vendors involved in weddings. The application offers convenience to couples-to-be and Wedding Organizers in viewing, organizing, and utilizing resources more effectively. With the application of the Round Robin method, it is anticipated that the operational efficiency of Wedding Organizers will improve, schedule conflicts will be mitigated, and the allocation of limited resources can be maximized. This study contributes to the advancement of a web-based Wedding Organizer scheduling.